2013
DOI: 10.1182/blood-2013-01-481184
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-mediated interaction of p210 BCR/ABL with β-catenin supports disease progression in a murine model for chronic myelogenous leukemia

Abstract: • p210 BCR/ABL interacts with b-catenin in the bone marrow transplantation model for chronic myelogenous leukemia.• Loss of the interaction results in an altered disease phenotype, suggesting a role for b-catenin in chronic phase disease.We have identified a ubiquitin-binding domain within the NH 2 -terminal sequences of p210 BCR/ABL and determined that the binding site co-localizes with the binding site for b-catenin. The domain does not support the auto-or trans-kinase activity of p210 BCR/ABL or its ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…CML stem cells appear to rely, among others, on the β-catenin/Tcf-Lef-dependent transcription program [16]. This pathway is aberrantly activated in CML mononuclear cells both in the chronic phase and the blast crisis stage [17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CML stem cells appear to rely, among others, on the β-catenin/Tcf-Lef-dependent transcription program [16]. This pathway is aberrantly activated in CML mononuclear cells both in the chronic phase and the blast crisis stage [17].…”
Section: Resultsmentioning
confidence: 99%
“…A great deal of attention has recently been paid to the role of signal transduction pathways involved in maintaining the self-renewal of leukemic cells. CML stem cells appear to rely, among others, on the β-catenin/Tcf-Lef-dependent transcription program [ 16 ]. This pathway is aberrantly activated in CML mononuclear cells both in the chronic phase and the blast crisis stage [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…CML is characterized by a chronic phase and a blast crisis and it was shown that β‐catenin is required for the progression from the chronic phase into blast crisis . Catenin activation in blast crisis may also be promoted by mis‐splicing of the upstream factor GSK‐3β, which may collaborate with increased BCR‐ABL–mediated pTyr654‐catenin phosphorylation . In addition, like in Hox‐A9/Meis1‐induced AML, activation of β‐catenin also promotes the self‐renewal properties of granulocytic progenitors (GMP) in CML …”
Section: The Role Of the Niche In Leukemogenesismentioning
confidence: 99%